PERANGKAT LUNAK PENGELOLAAN DATA ARSIP REKOMENDASI TEKNIS AIR TANAH DI BIDANG AIR TANAH DINAS ENERGI DAN SUMBER DAYA MINERAL PROVINSI JAWA BARAT - Andy Victor Pakpahan (Jurnal Teknologi Informasi, 2023)
The mining industry, the energy sector, the electrical sector, and the ground water sector are the four licensing service sectors provided by the Office of Energy and Mineral Resources of West Java Province, one of the government agencies. There are numerous issues with the administration of groundwater technical recommendation archive data, particularly in the realm of groundwater where this research was conducted. We therefore want a website-based program, i.e., a website that stores all historical information on technical suggestions for groundwater management and permits. Data may be produced with ease because data entry is simpler. Additionally, users of this website may find it simpler to submit routine reports. This website was created using Bootstrap and CSS, along with a number of other techniques. In the end, the groundwater staff will find it easier to manage groundwater technical suggestion archive data thanks to the services provided by this program for the Department of Energy and Mineral Resources. Due to the use of databases on the website, archival data and other data have been correctly maintained, and data can be readily searched using the current search tools and searched if the admin or officer is looking for the data he is looking for. We want to address difficulties by offering solutions on our website.